Early evidence reports positive outcomes after osteochondral grafts and chondrocyte transplantation in the hip: a systematic review. Issue 5 (9th August 2016) - Horner, Nolan S; Ekhtiari, Seper; Simunovic, Nicole; Bedi, Asheesh; Glyn-Jones, Siôn; Ayeni, Olufemi R
Abstract : Importance: To date, limited literature has explored the outcomes and indications for osteochondral grafts and chondrocyte transplantation in the hip. Objective: The purpose of this study was to evaluate the indications, investigations, rehabilitation strategies and clinical outcomes associated with treatment of hip cartilage defects with either autologous chondrocyte transplantation, osteochondral allografts, osteochondral autografts or synthetic osteochondral grafts. Evidence review: MEDLINE, EMBASE and PubMed were searched in duplicate for relevant studies, and data were abstracted from included studies. The Methodological Index for Non-Randomized Studies criteria were used to grade the quality of the studies. Findings: A total of 32 studies were included, involving 268 hips and 262 patients. Osteochondral grafts and chondrocyte transplantation were most commonly used for the treatment of osteochondral defects. The chondral lesions treated varied in size from 1 to 15.7 cm 2 . Positive outcomes were reported across numerous standardised outcome scores at a mean follow-up of 28.6 months. The overall complication rate was 3.4%. The rate of patients requiring further surgery was 9.5%. Conclusions: The outcomes reported in the literature on the treatment of hip chondral defects with osteochondral grafts and chondrocyte transplantation are generally positive at short-term to medium-term follow-ups. Low rates of complications and patients requiring further surgery were reported. The most common indications for these treatment options are full-thickness osteochondral defects larger than 2 cm 2 in young patients. The indications remain unclear when using these techniques to treat other pathology, including avascular necrosis. A period of 6–12 weeks of restricted weight bearing is recommended in the literature following these procedures. The quality of the literature that currently exists on this topic remains quite low.